Isoflavone Malonyltransferases GmIMaT1 and GmIMaT3 Differently Modify Isoflavone Glucosides in Soybean (Glycine max) under Various Stresses - Ahmad, Muhammad Z.; Li, Penghui; Wang, Junjie; Rehman, Naveed Ur; Zhao, Jian (Frontiers in Plant Science, 2017)
Malonylated isoflavones are the major forms of isoflavonoids in soybean plants, the genes responsible for their biosyntheses are not well understood, nor their physiological functions. Here we report a new BAHD family isoflavone glucoside malonyltransferase GmIMaT1, and GmIMaT3, which is allelic to the previously characterized GmMT7 and GmIF7MaT. Biochemical studies showed that recombinant GmIMaT1 and GmIMaT3 enzymes used malonyl-CoA and several isoflavone 7-O-glucosides as substrates. The Km values of GmIMaT1 for glycitin, genistin and daidzin were 13.11, 23.04, and 36.28 µM, respectively, while these of GmIMaT3 were 12.94, 26.67, and 30.12 µM, respectively. Transgenic hairy roots overexpressing both GmIMaTs had increased levels of malonyldaidzin and malonylgenistin, and contents of daidzin and glycitin increased only in GmIMaT1-overexpression lines. The increased daidzein and genistein contents were detected only in GmIMaT3-overexpression lines. Knockdown of GmIMaT1 and GmIMaT3 reduced malonyldaidzin and malonylgenistin contents, and affected other isoflavonoids differently. GmIMaT1 is primarily localized to the ER while GmIMaT3 is primarily in the cytosol. By examining their transcript changes corresponding to the altered isoflavone metabolic profiles under various environmental and hormonal stresses, we probed the possible functions of GmIMaTs. Two GmIMaTs displayed distinct tissue expression patterns and respond differently to various factors in modifying isoflavone 7-O glucosides under various stresses.